Ambroise Paré and Laurent Joubert, Knowledge and Beliefs about Pregnancy in 16th Century France - Bujak, Victoria (Studia Ceranea, 2024)
Our article is devoted to the science of female anatomy in the 16th century, particularly the practices and beliefs related to pregnancy and childbirth. We analysed the academic discourse presented in the Œuvres of Ambroise Paré (1510–1590), physician and surgeon, to compare it with the Erreurs Populaires by Laurent Joubert (1529–1583), physician and professor at Montpellier. Through our research, we were able to establish an overview of the knowledge, beliefs, and methods practiced at the time for treating the female body, not only in the medical field but also among the laypeople. Firstly, we examined the signs and progression of pregnancy as depicted in Paré’s Œuvres and Joubert’s Erreurs Populaires. Next, we focused on childbirth itself, the complications during delivery, and the solutions envisioned at the time to address them. After comparing these different discourses, we found that the approaches and objectives of these two physicians are quite distinct. Paré remains faithful to the theories of the ancients despite his extensive experience, whereas Joubert appears closer to practical applications in his attack on the numerous beliefs prevalent in society. However, while these differences significantly distinguish the two discourses and their targeted readerships differ in nature, both authors generally address the same questions and highlight the problems that women and physicians faced at the time.